Relationship between the resected stomach volume and early postoperative weight loss following laparoscopic sleeve gastrectomy - Salman, Mohammed Abd Allah; Elshazly, Mostafa; Ragab, Amr Ali; Hegazy, Tarek osama (International Surgery Journal, 2018)
Background: The aim of the study was evaluation of the effect of the resected gastric volume (RGV) on weight loss after laparoscopic sleeve gastrectomy (LSG). Methods: This prospective study included 40 morbidly obese patients undergoing LSG. Multi Detector Computed Tomography (MDCT) was used to measure preoperative stomach volume and sleeve volume. The actual RGV was measured after surgery. The primary outcome measure was the relation between RGV and percentage of excess body weight loss (%EBWL) after 3 and 6 months. The secondary outcome was early postoperative complications. Results: The mean preoperative BMI was 43.5±4.3 kg/m2. The actual RGV was substantially correlated with that estimated by CT (r=0.996, p<0.001). The former was significantly larger with a mean deviation of 17.6 cc (95%CI: 12.2-23.0 kg). The actual and CT-estimated RGV were positively correlated with% EBWL after 3 months (r=0.361, p=0.022 and r=0.471, p<0.001, respectively) and after 6 months (r=0.466, p=0.002 and r=0.553, p<0.001, respectively). Percentage of volume reduction was positively correlated with weight reduction after 3 and 6 months (r=0.0.525, p=0.001 and r=0.564, p<0.001, respectively). Conclusions: The resected gastric volume during LSG was significantly correlated with weight reduction after 3 and 6 months of surgery. Sleeve volume was not correlated with early weight reduction. MDCT is a reliable method to measure gastric volume before and after surgery.